(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study aims to analyse the influence of inflation rates and interest rates on foreign exchange rates for the period from 2000 to 2023. Using secondary data, this study applied a multiple linear regression method. The analysis results show that inflation has a negative and statistically significant effect on the exchange rate. On the other hand, interest rates have no significant impact on the exchange rate. Simultaneously, inflation and interest rates have a significant effect on the exchange rate. These findings underscore the importance of adaptive monetary policy and monitoring of external factors in maintaining exchange rate stability and the national economy.